2018
DOI: 10.1021/acsami.8b02994
|View full text |Cite
|
Sign up to set email alerts
|

Rapid on-Chip Assembly of Niosomes: Batch versus Continuous Flow Reactors

Abstract: The large-scale continuous production of niosomes remains challenging. The inherent drawbacks of batch processes such as large particle polydispersity and reduced batch-to-batch reproducibility are here overcome by using commercially available microfluidic reactors. Compared to the traditional batch-based film hydration method, herein, we demonstrate that it is possible to carry out the homogeneous, large-scale (up to 120 mg/min) production of niosomes using two different synthesis techniques (the thin film hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
(124 reference statements)
0
11
1
Order By: Relevance
“…Regarding temperature effect some authors reported an increase in particle size as temperature increased [24] which were attributed to the bilayer expansion at higher temperature [43]. In our case, such increase in particle size was not observed.…”
Section: Figurecontrasting
confidence: 53%
See 1 more Smart Citation
“…Regarding temperature effect some authors reported an increase in particle size as temperature increased [24] which were attributed to the bilayer expansion at higher temperature [43]. In our case, such increase in particle size was not observed.…”
Section: Figurecontrasting
confidence: 53%
“…By controlling the flow, the extension of mixing and hence the size of liposomes, could also be controlled. However, the production of niosomes through microfluidic routes remains less explored, and limited attention has been paid to using HFF technique [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have proven niosomes to be safe without any cytotoxic effects. 34,64,65 As could be seen from (Fig. 3), the cellular viability was above 80% in all the cell lines even at high concentration of particles (1000 mg ml À1 ).…”
Section: Cytocompatibility Analysismentioning
confidence: 66%
“…Surfactants, most often supplemented with cholesterol (Chol), can form bilayer vesicles known as niosomes . Niosomal formulations are capable of encapsulating hydrophilic and hydrophobic drugs in the aqueous core and the lipophilic membrane, respectively . Niosomes have been extensively used in the cosmetic industry and studied for topical drug delivery for decades .…”
Section: Introductionmentioning
confidence: 99%
“…Novel manufacturing strategies are to be investigated for producing diverse formulations. Recently, microfluidics was utilized to produce conventional niosomes; however, it was not possible to incorporate a Chol content higher than equimolar with this technique either . In this study, we utilized a staggered herringbone micromixer (SHM) to engineer nano‐sized vesicles with a high Chol content (>50 mol%).…”
Section: Introductionmentioning
confidence: 99%